IMPLEMENTASI PEMBELAJARAN MAH??RAH KALAM?? DI UNSUDA LAMONGAN - arif widodo arif (Program Studi Pendidikan Bahasa Arab Fakultas Tarbiyah IAI Al-Qur'an Al-Ittifaqiah Indralaya, 2025)
Abstract This qualitative research examines the implementation of mah??rah kal??m (Arabic speaking skills) learning in the Arabic Language course at the University (UNSUDA) of Lamongan. The learning was conducted every Wednesday for one semester using a communicative approach and interactive materials. Data were collected through classroom observations, in-depth interviews with lecturers and students, documentation (video recordings of activities), and field notes. Key findings included: (1) student motivation level of 80%; (2) active participation in lectures 90%; (3) student assessment of interactive materials 90%; and (4) intensive question and answer practice during lectures. The thematic analysis indicates that the combination of a communicative approach, interactive materials, and formative feedback mechanisms plays a significant role in improving student participation and speaking confidence. Practical implications and recommendations for curriculum development and teaching practices are discussed.